There may be more than meets the eye with Clostridium perfringens bacteremia - Stephen Melnick; Salik Nazir; Brian Chwiecko; Benjamin Lloyd (Greater Baltimore Medical Center, 2017)
We present the case of an 89-year-old man with a 1 month history of fevers and fatigue. Blood cultures were positive for Clostridium perfringens. The patient had worsening abdominal distension in which an abdominal computed tomography scan uncovered a colonic mass, and further work-up revealed poorly differentiated adenocarcinoma. The patient was treated with antibiotics, but unfortunately, given his age and the new malignancy, he was discharged to hospice care. The association between clostridial bacteremia and colon cancer has been well described in the literature and is further discussed in this article. This case highlights the importance of recognizing possible occult malignancy in the right clinical setting in patients found to have clostridial bacteremia.